2015
DOI: 10.1523/eneuro.0102-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Rapid Air-Borne Odor Tracking without Casting

Abstract: Casting behavior (zigzagging across an odor stream) is common in air/liquid-borne odor tracking in open fields; however, terrestrial odor localization often involves path selection in a familiar environment. To study this, we trained rats to run toward an odor source in a multi-choice olfactory arena with near-laminar airflow. We find that rather than casting, rats run directly toward an odor port, and if this is incorrect, they serially sample other sources. This behavior is consistent and accurate in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
1
39
1
Order By: Relevance
“…There is currently little information available on how terrestrial animals track airborne odors [14,31], with most information coming from studies using invertebrates [15]. Here, we used controlled laboratory conditions to demonstrate that mice can make use of airborne odor cues to locate a source.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently little information available on how terrestrial animals track airborne odors [14,31], with most information coming from studies using invertebrates [15]. Here, we used controlled laboratory conditions to demonstrate that mice can make use of airborne odor cues to locate a source.…”
Section: Discussionmentioning
confidence: 99%
“…One way to ameliorate this problem is to use a Mass Flow Controller (MFC) to vary the airflow through a scintillation vial containing pure odorants ( Supplementary Fig. 1im) 8,23,27,28 . The concentration of odorant in the odorized airstream depends only on the flow rate of the MFC and it is stable over time as far as there is some odorant left in the vial and the air is blown continuously through it (and sent to exhaust).…”
Section: How To Estimating the Dose-response Curve Of An Olfactory Nementioning
confidence: 99%
“…). Similarly, experimental elevation of turbulence levels caused rats to take longer to find odor sources (Bhattacharyya and Bhalla ). Other studies have shown turbulence to have no effect on avian nest survival (Conover et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sharp-tailed grouse (Tympanuchus phasianellus) loafing locations were characterized by higher turbulence and updraft than random points (Conover and Borgo 2009), and high turbulence levels reduced the probability that hunting dogs (Canis lupus familiaris) and blue crabs (Callinectes sapidus) located odor sources (Weissburg and Zimmer-Faust 1994, Conover 2007, Jackson et al 2007. Similarly, experimental elevation of turbulence levels caused rats to take longer to find odor sources (Bhattacharyya and Bhalla 2015). Other studies have shown turbulence to have no effect on avian nest survival (Conover et al 2010, Fogarty et al 2017) and simulated prey persistence (Ruzicka and Conover 2012) or to actually increase foraging efficiency over a short distance in an aquatic environment (Ferner and Weissburg 2005).…”
Section: Introductionmentioning
confidence: 99%